Wideband Multi-Resonant Microstrip Patch Antenna for Wireless Communication Systems - Mia Maria Ulfah; Rheyuniarto Sahlendar Asthan (LPPM Universitas Negeri Semarang, 2025)
The increasing demand for high-performance wireless communication systems has driven the development of compact antennas that can support wideband operation, particularly in the 5 GHz frequency range. Microstrip patch antennas (MPAs) remain attractive for such applications due to their low profile and ease of integration, although achieving a wide impedance bandwidth remains a key challenge. This paper presents a low-profile MPA with a wideband response designed for the 5 GHz band of wireless communication systems. The proposed MPA is implemented on a single-layer FR-4 substrate with a thickness of 1.6 mm and is excited using a coaxial probe feed. To achieve a wide impedance bandwidth, a U-shaped patch is utilized as the primary radiator, complemented by a slot, a parasitic element, and a rectangular ring surrounding the main resonator, aiming to generate multiple resonant modes and improve impedance matching. The influence of each modification on antenna performance is systematically analyzed. To validate its performance, the proposed MPA is fabricated and measured, with the obtained results compared to the simulated ones. Simulation and measurement results show good agreement, confirming that the proposed MPA achieves a wideband response with a fractional bandwidth of 18.8% and a peak realized gain of 4.85 dBi. These results highlight the effectiveness of the proposed design and demonstrate its potential for compact and wideband wireless communication devices operating around 5 GHz frequency range.